2017
DOI: 10.9746/jcmsi.10.156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cruising Speed on Steering Oscillations of Car Induced by Modeled Cognitively Impaired Human Driver

Abstract: : In this paper, we proposed an approach that uses genetic programming (GP) to automatically develop a driving agent -as a model of a human driver -to optimally steer a realistically simulated car with an instant, non-latent steering response. Using the latter, we tested the hypothesis that introducing a delay in the steering response of an evolved model of a human driver results in well-expressed steering oscillations. We further evaluated the effects of speeding on the steering oscillation and observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Sharma [8] observed that cognitive load on a driver might impair him cognitively, which might in turn cause a steering oscillation leading to accidents. The research performed simulations to evolve a model of a driving agent that could control a car as well as recognize a possible distraction of a driver.…”
Section: On Driver's Distraction and Emergency Brakingmentioning
confidence: 99%
“…Sharma [8] observed that cognitive load on a driver might impair him cognitively, which might in turn cause a steering oscillation leading to accidents. The research performed simulations to evolve a model of a driving agent that could control a car as well as recognize a possible distraction of a driver.…”
Section: On Driver's Distraction and Emergency Brakingmentioning
confidence: 99%